Exploring the Effects of Betamethasone on Total Fetal Lung Volume and Its Relationship in the Prediction of Neonatal Respiratory Distress Syndrome - Dzikova, Elena; Dimitrov, Goran; Aleksioska Papestiev, Irena; Tofiloska, Valentina (Mакедонско лекарско друштво = Macedonian medical association/De Gruyter, 2023)
Introduction. Every year, 15 million infants are born prematurely, and 1 million of them surrender to preterm birth complications, accounting for 1 in every 3 neonatal deaths. Globally, about 28.5 premature births occur per minute, resulting in approximately 4 fatalities, with 2 of these attributed to respiratory distress syndrome (RDS). This study aimed to investigate how betamethasone affects fetal lung development by assessing fetal lung volume and its association with neonatal RDS. The study received ethical approval by the Ethics Committee of the Faculty of Medicine, Ss. Cyril and Methodius University in Skopje, North Macedonia. Methods. This prospective clinical observational-interventional study involved 100 patients, including 50 with a history of preterm birth (study group) and 50 full-term cases (control group). The study was conducted at the University Clinic for Gynecology and Obstetrics, Faculty of Medicine, Ss. Cyril and Methodius University in Skopje, North Macedonia. Fetal lung volume was measured before and after betamethasone therapy, and its relation to neonatal RDS was evaluated. Patients were categorized into five groups based on gestational weeks. Results. Significant differences in total fetal pulmonary volume were observed before and after betamethasone treatment. Additionally, the measurement of total fetal lung volume has proved to be effective in predicting neonatal respiratory distress syndrome. Conclusion. Total fetal pulmonary volume measurement is a highly sensitive and specific method for predicting fetal lung maturity. This non-invasive, cost-effective, and easily accessible technique can be routinely employed in hospitals equipped with suitable ultrasound devices and adequately trained staff.
ИСТРАЖУВАЊЕ НА ЕФЕКТОТ НА БЕТАМЕТАЗОН ВРЗ ВКУПНИОТ ФЕТАЛЕН БЕЛОДРОБЕН ВОЛУМЕН И НЕГОВАТА УЛОГА ВО ПРЕДИКЦИЈА НА НЕОНАТАЛЕН РЕСПИРАТОРЕН ДИСТРЕС СИНДРОМ
Keywords: fetal total pulmonary volume; fetal lung maturity; respiratory distress syndrome